Alleys of Your Mind Augmented Intelligence and Its Traumas - Pasquinelli, Matteo (meson press, 2015)
What does thinking mean in the age of Artificial Intelligence? How is big-scale computation transforming the way our brains function? This collection discusses these pressing questions by looking beyond instrumental rationality. Exploring recent developments as well as examples from the history of cybernetics, the book uncovers the positive role played by errors and traumas in the construction of our contemporary technological minds. With texts by Benjamin Bratton, Orit Halpern, Adrian Lahoud, Jon Lindblom, Catherine Malabou, Reza Negarestani, Luciana Parisi, Matteo Pasquinelli, Ana Teixeira Pinto, Michael Wheeler, Charles Wolfe, and Ben Woodard.